Emerging IP monetisation solutions: the institutionalisation of an IP exchange. (1st January 2012) - Ghafele, Roya; Gibert, Benjamin; Malackowski, James
This paper examines whether moving licensing from the traditional bilateral contract model to an exchange model will lead to more efficient price discovery and, ultimately, more liquidity in the market for IP rights transfer. Using the recently created Chicago-based Intellectual Property Exchange International (IPXI) as a model, we address the rationale for such an exchange and the mechanisms by which it can operate. We contend that IPXI's business model, which is built around unit licence right (ULR) contracts – which may be seen as a paid-up non-exclusive licence to the purchaser – addresses some of the current inefficiencies in IP management. However, the market efficiency that is needed to turn IP rights into a liquid asset inevitably takes time to evolve. Without community support for and participation in the exchange, from both buyers and sellers, the market cannot be established.